Centrilobular emphysema and panlobular emphysema: two different diseases. Issue 5 (September 1973) - Anderson, A. E.; Foraker, Alvan G.
Abstract : Anderson, A. E., and Foraker, A. G. (1973). Thorax, 28, 547-550. Centrilobular emphysema and panlobular emphysema: two different diseases. Twenty-one cases of centrilobular emphysema and 19 cases of panlobular emphysema, previously so designated according to recommended criteria, were reassessed for differences in zonal distribution within lungs through systematic sampling and statistical comparisons. Characteristic distribution profiles were defined for the two forms of disease. Centrilobular emphysema appeared to be mainly a disease of the upper lobe and the apices within the upper and lower lobes. In contrast, panlobular emphysema was a more or less diffuse process within lobes and lungs with mild preferential involvement of the lower lobe. These regional trends coupled with the typical appearance of individual lesions within lobules are considered to provide strong support for the contention that centrilobular emphysema and panlobular emphysema are morphologically distinct entities. Probable reasons for difficulties in differentiating some examples of centrilobular and panlobular emphysema are given. The need for further clarification of associated and background factors is stressed.